Should I stay, or should I go?: self-legitimacy of attorneys in an authoritarian state - Khalikova, Yulia (Crime, law and social change, 2021)
In non-democracies, lawyers face various constraints ranging from the absence of acquittals or violations of their clients’ rights to threats and criminal proceedings against them. Yet, we know little about the working conditions of attorneys’ in authoritarian regimes, and what influences their desire to remain in the profession. Using a survey of attorneys in Russia, our study demonstrates which factors impact the desire to stay in the profession and how self-legitimacy influences these choices. We find that the frequency of violations of their clients’ rights by law enforcement agencies undermines self-legitimacy of attorneys. In turn, this increases the attorneys’ willingness to leave the profession, which is mitigated by two factors. First, attorneys with closer contacts with their colleagues in the regional bar associations are less willing to leave the bar for other career options. Second, when such associations actively exclude their members for violations of professional ethics, bona fide attorneys are more willing to stay. Lastly, we find that the expressed desire of leaving the profession transforms into actual voluntary leave in the following year. These findings have important implications, as attorneys do not only defend their clients but can also influence the political regime, either through the mobilisation of law or engaging into collective actions with their colleagues.